Przestrzenne zagadnienia dynamiczne ośrodków niesprężystych - Bejda, J. (Engineering Transactions, 1969)
In the paper the problem of waves propagation in elastic-plastic and elastic/viscoplastic material is critically analysed and discussed. The harmonic analysis and the analysis based on the propagation of weak discontinuities for two-dimensional plasticity and viscoplasticity is given. Some interesting observations and conclusions concerning the velocity of elastic, elastic-plastic, and elastic/viscoplastic waves are obtained. In particular the problem of plane waves on the basis of harmonic, bicharacteristics and dislocation theory is discussed.